Mopani wood utilisation and management perceptions of rural inhabitants in the Greater Giyani Municipality, Limpopo Province - Makhado, Rudzani Albert (My University, 2008)
This study reports the findings about the utilisation and management of mopane woodland resources by rural inhabitants in the Greater Giyani Municipality, Limpopo Province. The main aim was to quantify the amount of wood and other non-wood products used by villagers and to determine their perceptions on woodland resources management. Mopane woodland is an essential source of firewood and poles used for construction of traditional structures. The role played by non-wood products in the socio-economic wellbeing of villagers was also assessed. In six sampled villages in the Greater Giyani Municipality, a total of 180 villagers were interviewed, together with 13 traditional leaders and 10 conservation officials. Three villages were located in woodland depleted areas and three in woodland abundant areas. Semistructured and participatory approaches were followed to obtain data on mopane woodland resources utilisation, conservation and perception of villagers on woodland resources management. The amount of wood used by villagers for firewood and construction was quantified by weighing and measuring the length, circumference and diameter of the poles. Mass and volume of wood used by a household for firewood and construction was also estimated. Colophospermum mopane is the first choice for villagers for firewood and in construction of traditional structures. Villagers also obtain traditional medicines from woodland, and mopane worms as a nutritional supply and for generating household income. Notwithstanding the value of mopane woodland resources to rural life, woodland resources are over-harvested (as a result of poverty) and mis-managed. This was intensified by lack of responsibility in the management of woodland and lack of capacity within the municipality to enforce conservation regulation. Lower levels of participation in woodland management have resulted in higher levels of woodland degradation. Most villagers perceive woodland resources as common property, giving themselves rights over the use of such resources. These factors have increased the likelihood of illegal harvesting of woodland resources and overall depletion of the surrounding woodland resources, depriving communities from the full range of benefits that derived from woodland. Changes in woodland management regimes in rural areas were examined and possible options to promote sustainable use of woodland resources in rural areas were proposed.
Thesis (M.Sc. (Botany)) -- University of Limpopo, 2008
Keywords: Colophospermum mopane; Management; Firewood; Mopane worms; Poles; Woodland resources; Wood -- Utilization -- South Africa -- Limpopo; Fuelwood; Mopane tree